A computational model for investigating the effects of changes in bioavailability of insulin-like growth factor-1 on the homeostasis of the intervertebral disc. (1st November 2016) - Elmasry, Shady; Asfour, Shihab; de Rivero Vaccari, Juan Pablo; Travascio, Francesco
Abstract: Insulin-like growth factor-1 (IGF-1) is well-known for upregulating cell proliferation and biosynthesis of the extracellular matrix in the intervertebral disc (IVD). Pathological conditions, such as obesity or chronic kidney disease cause IGF-1 deficiency in plasma. How this deficiency impacts disc homeostasis remains unknown. Pro-anabolic approaches for the treatment of disc degeneration based on enhancing IGF-1 bioavailability to tissue-cells are considered, but knowledge of their effectiveness in enhancing cellular anabolism of a degenerated disc is limited. In this study, we developed a computational model for disc homeostasis specifically addressing the role of IGF-1 in modulating both extracellular matrix biosynthesis and cellularity in the IVD. This model was applied to investigate how changes in IGF-1 bioavailability, namely deficiency or enhancement of growth factor, affect disc health. In this study, it was found that IGF-1 deficiency mainly affects the biosynthesis of ECM components, especially in the most external regions of the IVD such as the cartilage endplates and the outer portion of annulus fibrosus. Also, a total of three approaches for increasing IGF-1 bioavailability as a therapy for degenerated IVDs were investigated. It was found that all these strategies are only beneficial to those disc regions receiving sufficient nutritional supply (i.e., the outmost IVD regions), while they exacerbate tissue degradation in malnourished regions (i.e., inner portion of the disc). This suggests that pro-anabolic growth factor-based therapies are limited in that their success strongly depends on an adequate nutritional supply to the IVD tissue, which is not guaranteed in degenerated discs. Highlights: Low levels of IGF-1 in plasma decreases cellular anabolism in IVD. Impaired nutritional supply to the disc decreases both cellular anabolism and viability. Pro-anabolic treatments for IVD degeneration based on enhancing IGF-1 bioavailability must include delivery of nutrients to disc cells.